2021
DOI: 10.1186/s12944-021-01597-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of comorbid hypertriglyceridemia and abdominal obesity in the severity of acute pancreatitis: a retrospective study

Abstract: Background The effect of comorbid hypertriglyceridemia (HTG) and abdominal obesity (AO) on acute pancreatitis (AP) remains unclear. The aim of this study was to explore the effect of comorbid HTG and AO and discuss which is the dominant disorder. Methods In this study, 1219 AP patients who presented with HTG or AO were stratified into four groups: non-HTG + non-AO, HTG + non-AO, non-HTG + AO, and HTG + AO. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…29 In contrast, males contributed to approximately 50% of AP from other etiologies, wherein their average age were 10 years higher than in HTG-AP group. Similarly, a recent large study from China 31 conducted between 2016 and 2020 with 614 patients with HTG-AP reported that approximately 70% of the patients were males and the average age of presentation was in the mid-40s. Again, the age of presentation with non-HTG-AP was significantly higher, with an average of 60 years and males comprising 43%-52% of the non-HTG-AP group.…”
Section: Demographicsmentioning
confidence: 87%
“…29 In contrast, males contributed to approximately 50% of AP from other etiologies, wherein their average age were 10 years higher than in HTG-AP group. Similarly, a recent large study from China 31 conducted between 2016 and 2020 with 614 patients with HTG-AP reported that approximately 70% of the patients were males and the average age of presentation was in the mid-40s. Again, the age of presentation with non-HTG-AP was significantly higher, with an average of 60 years and males comprising 43%-52% of the non-HTG-AP group.…”
Section: Demographicsmentioning
confidence: 87%
“…Although the age with non–HTG-AP was significantly higher, with an average of 60 years and males comprising 43% to 53% of the non–HTG-AP group. [20] Overall, the typical age of patients with HTG-AP is middle-aged and males are much more exposed than females.…”
Section: Epidemiology and Demographicsmentioning
confidence: 99%
“…The mechanism via which obesity leads to SAP has been a topic of study for ages. Hypertriglyceridemia is an independent risk factor for local complications and persistent organ failure [11,12] . Pancreatic lipases can induce the lipolysis of adipocyte triglycerides to non-esteri ed free fatty acids (NEFA).…”
Section: Introductionmentioning
confidence: 99%